Multiple Coenurus cerebralis Cysts Detected in a Sheep Brain and Molecular Characterization of the Individual Cysts - Celik, Figen; Tekin, Afra Sena; Uslug, Muhammet; Simsek, Sami (Ist Zooprofilattico Sperimentale Abruzzo & Molise G Caporale-Izs A&M, 2025)
Taenia multiceps is found in canids and in its larval stage is known as Coenurus cerebralis causes coenurosis. The disease has a significant impact on the economic value of sheep and goats. The aim of the current study was to identify multiple cysts in the brain of a sheep displaying common symptoms of C. cerebralis and to amplify and sequence analyse the mitochondrial cytochrome oxidase subunit 1 gene of each individual cyst by PCR. The research material used was the head of a sheep exhibiting neurological symptoms. Seven cysts associated with C. cerebralis were detected in the brain upon thorough examination. The mt-CO1 gene was amplified by PCR, and all isolates were sequenced. Sequence alignment revealed the presence of point mutations, and 20 polymorphic sites were identified, of which 7.7% (1/13) were parsimony informative. The isolates demonstrated significant haplotype diversity and low nucleotide diversity. In this study, only one isolate obtained from Turkey belonged to the fourth main haplotype, while the remaining six isolates constituted a distinct and unique single haplotype. This is the first time that haplotypic distinctions have been identified among isolates obtained from a sheep brain that is multiply infected with C. cerebralis.
Keywords: Coenurus cerebralis; haplotype; mt-CO1; PCR; sheep; Taenia multiceps